The intelligent enterprise in the era of big data - Srinivasan, Venkat, 1956- (John Wiley & Sons, 2016)
An innovative guide to the organization and function of enterprises in the technological age In the era of big data and automation, this book presents a cutting-edge approach in how enterprises should organize and function. Striking a practical balance between theory and practice, The Intelligent Enterprise in the Era of Big Data presents an enterprise architecture that embodies the power of the emerging technology environment. Beginning with an introduction to the key challenges that enterprises face, the book systematically outlines a modern enterprise architecture through a detailed discussion of the inseparable elements of such an architecture: efficiency, flexibility, and intelligence. This architecture enables rapid responses to market needs by facilitating intelligent, flexible automation of enterprise business processes and sensing important developments in internal and external environments in near real time. Illustrating all of these elements in an integrated fashion, The Intelligent Enterprise in the Era of Big Data also features: -A detailed discussion on issues of time-to-market and flexibility with respect to enterprise application technology -Novel analyses illustrated through extensive real-world case studies to help readers better understand the applicability of the architecture and concepts -Practical approaches for designing and building intelligent enterprises -An appendix that presents various approaches to text analysis with real-world business implications The Intelligent Enterprise in the Era of Big Data is an appropriate reference for business executives, information technology professionals, data scientists, and management consultants. - Resumé vydavatel
Keywords: podnikový management; big data; industrial management; příručky; elektronické knihy; handbooks and manuals; electronic books